Poor sleep quality and its associated factors among nurses in tertiary hospitals, Kelantan - Supian, Nur Shuhaiza (2024)
Introduction: Understanding the significance of good sleep quality will help to improve quality of healthcare services and enhance patient safety. Thus, the purpose of this study was to determine poor sleep quality and its associated factors among nurses in tertiary hospitals in Kelantan. Methodology: This cross-sectional study examines nurses from two tertiary hospitals in Kelantan, Malaysia. The nurses were proportionately and randomly selected from the hospitals and included in the study. The nurses worked in tertiary hospitals and had at least two months of working experience in current department. The study used self-administered questionnaire with 19 items in seven component scores. The data were analysed using SPSS version 28 and logistic regression analyses were used to identify the associated factors. Results: A total of 470 nurses participated in this study. The results indicate that prevalence of poor sleep quality among nurses was 69.8%. The study identifies the sleep duration (aOR 0.291; 95% CI: 0.215,0.393; p<0.001), working experience (aOR 0.953; 95% CI: 0.924, 0.984; p=0.003), history of involvement in medication error (aOR 2.669; 95% CI: 1.413, 5.041; p=0.002) and commuting injury (aOR 1.869; 95% CI: 1.119, 3.121; p=0.017) as the significant associated factors. Conclusion: The study found that nurses generally had poor sleep quality with some significant associated factors. To improve sleep quality among nurses, ongoing education and establishing a nurturing work environment are important.